Application of the STAD Type Cooperative Learning Model to Improve Mathematics Learning Outcomes in Students of the Aisyiah Pandan Guidance Studio Kuala Lumpur Malaysia - Maylida, Cut; Sari, Suci Perwita (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effectiveness of implementing the Cooperative Learning model of the Student Teams Achievement Division (STAD) type in improving students' mathematics learning outcomes at Sanggar Bimbingan ‘Aisyiyah Pandan, Kuala Lumpur, Malaysia. The method used in this research is classroom action research (CAR) conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this study were 20 eighth-grade students participating in a tutoring program. The instruments used included observation sheets, learning outcome tests, and documentation. The results showed an improvement in students’ learning outcomes from cycle I to cycle II. The average student scores increased significantly, and students’ learning activities also showed positive changes. Thus, the STAD learning model is effectively applied to improve mathematics learning outcomes in tutoring settings, especially for students with diverse educational backgrounds.